2017
DOI: 10.3389/fmicb.2017.00345
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Humanized Antibody against the Sporothrix Antigen, gp70, in Promoting Phagocytosis and Reducing Disease Burden

Abstract: Sporotrichosis is a subcutaneous mycosis distributed worldwide and is frequently reported in countries with tropical climates, as Latin America countries. We previously demonstrated that mice with sporotrichosis produce specific antibodies against a 70-kDa fungal protein, indicating that specific antibodies against this molecule may help to control the sporotrichosis. IgG1 monoclonal antibody was generated, and called mAbP6E7, in mice against a 70-kDa glycoprotein (gp70) of S. schenckii. The mAbP6E7 showed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…Bifidobacterium , including its metabolite acetate, a short-chain fat acid, has been shown to modulate the gut microbiota and the immune system [ 24, 25 ]. In our previous pre-clinical study, we found that non-viable components of the bacterium or its metabolite acetate partially ameliorated the cognitive decline observed in an AD mouse model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium , including its metabolite acetate, a short-chain fat acid, has been shown to modulate the gut microbiota and the immune system [ 24, 25 ]. In our previous pre-clinical study, we found that non-viable components of the bacterium or its metabolite acetate partially ameliorated the cognitive decline observed in an AD mouse model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibodies against Sporothrix antigens could be detected throughout the infection in mice (20). Anti-Gp70 is one of the antibodies that has been widely recognized as playing protective role against S. schenckii and S. brasiliensis infection (21,22). Recently, anti-enolase antibodies were also characterized involved in antifungal responses in S. schenckii and S. brasilensis infected mice (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…An IgG 1 raised against a 70 kDa glycoprotein and putative adhesin protected mice from this pathogen when administered either before, during, or even three days after infection [68,69]. A humanized version of this IgG 1 , given 3d post infection, also reduced the fungal burden in the spleens, but not in livers of infected mice [70].…”
Section: Protective Antibodies Against Dimorphic Fungimentioning
confidence: 99%